Analysis of Solid Waste Generation, Composition, and Economic Potential Using Cost-Benefit Analysis Method - Shintia Nur Asiah; Suci Wulandari; Aulia Annas Mufti; Andika Munandar; Nabila Putriyandri Alifa; Alien Abi Bianasari (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
The Natar market is experiencing an increase in solid waste generation that has not been resolved optimally due to inadequate Temporary Waste Storage Site facilities and a lack of awareness, causing waste accumulation and the transfer of problems to the landfill. This study aimed to analyze solid waste generation and composition based on SNI 19-3964-1994 and to assess the economic potential of recycled waste and the cost-benefit analysis for organic waste processing. The amount of waste produced at the Natar Market was 884.45 kg per day and 7,902.33 liters per day. The composition of solid waste is dominated by organic waste (87.34 %), Low-Density Polyethylene plastic (8.70 %), paper/cardboard (2.14 %), Polyethylene Terephthalate plastic (1.27 %), and other types of waste less than 1%. The selected waste processing alternative was the Black Soldier Fly technology, with a scoring and weighting result of 418 points. Recycled waste has the potential to generate an economic value of IDR 2,151,796.50. The cost-benefit analysis shows that Black Soldier technology is feasible to implement with a Net Present Value of IDR 497,543,239.61, an Internal Rate of Return of 12%, and a Benefit Cost Ratio of 1.017.